2021
DOI: 10.1007/s10984-021-09352-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of Online Classroom Learning Environment Inventory (OCLEI): The case of Indonesia during the COVID-19 pandemic

Abstract: This paper reports the development and validation of a new questionnaire to assess students' perceptions of the online learning environment in Indonesia during the COVID-19 pandemic. In total, 669 participants (454 women, 215 men) from various universities were recruited online to complete a 25-item questionnaire. Item factor analysis verified a five-factor model, while multidimensional Rasch analysis showed that all items fit this model and have good reliability. The factors of Access, Interaction, Lecturer S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Because of the unfortunate timing of the disruption in the USA in the middle of the semester, data collection and corresponding research stopped. However, Rahayu et al ( 2021 ) accomplished the development and validation of the Online Classroom Learning Environment Inventory (OCLEI) in Indonesia and measured learning environments in newly-created online learning situations. Additionally, Howard et al ( 2020 ) investigated teacher self-efficacy beliefs and perceived institutional support associated with online instruction, which also are salient to teaching during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unfortunate timing of the disruption in the USA in the middle of the semester, data collection and corresponding research stopped. However, Rahayu et al ( 2021 ) accomplished the development and validation of the Online Classroom Learning Environment Inventory (OCLEI) in Indonesia and measured learning environments in newly-created online learning situations. Additionally, Howard et al ( 2020 ) investigated teacher self-efficacy beliefs and perceived institutional support associated with online instruction, which also are salient to teaching during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Different from conventional environments, technology-enhanced learning environments might affect students' learning experience, emotional perception, and class interaction (Haro et al, 2019). By contrast, cloud classroom learning environments might face various challenges, such as teachers' insu cient technology skills and incapability of dealing with technological problems during classes, which can have an opposite impact on students learning experience (Rahayu et al, 2021). Another issue this learning environment affected is the absence of effective supervision to students' behavior (Roddy et al, 2017).…”
Section: Characteristics Of Students and Cloud Classroom Learning Environmentsmentioning
confidence: 99%
“…To make sure "stop classes but never stop learning" in the epidemic, all high schools in China have carried out cloud classrooms through live broadcast platforms such as Ding Talk by Ali, Super Star Learning System, Rain classroom, MOOC, QQ, and Tencent Meeting, etc. Besides China, numerous countries have been dedicated to educational technology along with the unceasing development of information technology (Rahayu et al, 2021). Education methods, hence, has been greatly in uenced and online teaching is gradually prominent for greater advantages in many ways.…”
Section: Introduction Of Cloud Classroomsmentioning
confidence: 99%
“…After we found that the model fitted the data, the CFA analysis results were then used for the application of the multidimensional Rasch model. EFA and CFA provide important information about the instrument's dimensionality before applying the Rasch model analysis (Rahayu et al, 2021). For CFA, we employed the MPLUS 8.4 program with a robust maximum likelihood estimation method.…”
Section: Factor Analysismentioning
confidence: 99%
“…Initially, the Rasch model assumes that the instrument being analyzed has a single dimension (unidimensional). However, along with the need to analyze instruments with multidimensional factor structures, a multidimensional Rasch analysis has been developed (Adams et al, 1997;Rahayu et al, 2021). Although it has been developed for quite a long time and used in analyzing environmental attitude measures (see Kaiser et al, 2007), an application of the multidimensional Rasch analysis in environmental research in Indonesia has not been found.…”
Section: Introductionmentioning
confidence: 99%